Capsaicin protects cardiomyocytes against lipopolysaccharide-induced damage via 14-3-3γ-mediated autophagy augmentation - Qiao, Yang; Wang, Liang; Hu, Tianhong; Yin, Dong; He, Huan; He, Ming (Frontiers in Pharmacology, 2021)
Background: The myocardium is susceptible to lipopolysaccharide (LPS)-induced damage in sepsis, and cardiac dysfunction is a leading cause of mortality in patients with sepsis. The changes in cardiomyocyte autophagy in sepsis and the effects and mechanism of action of capsaicin (Cap) remain unclear. Methods and Results: The potential pathway of 14-3-3γ-dependent autophagy and the effects and mechanisms of Cap were studied in LPS-induced injury to primary cultured neonatal rat cardiomyocytes. The results showed that cardiomyocyte viability decreased, lactate dehydrogenase and creatine kinase activities increased, 14-3-3γ expression was downregulated, and autophagy was inhibited after LPS challenge. Cap pretreatment augmented autophagy by upregulating 14-3-3γ expression and activating AMP-activated protein kinase (AMPK) and unc-51 like autophagy-activating kinase 1 (ULK1), suppressing mammalian target of rapamycin (mTOR), alleviating cardiac dysfunction and improving the inflammation response, whereas pAD/14-3-3γ-shRNA nullified the above effects. Cap pretreatment also decreased the levels of IL-1β, TNF-α, IL-6, and IL-10; suppressed intracellular oxidative stress; reduced the intracellular/mitochondrial reactive oxygen species (ROS); balanced GSH/GSSG; increased GSH-Px, catalase, and SOD activities; and decreased MDA contents. It also increased ATP content, activated complex Ⅰand complex Ⅲ, stabilized the mitochondrial membrane potential, and decreased the mitochondrial permeability transition pore opening, thereby improving mitochondrial function. Conclusion: Pretreatment with Cap can regulate autophagy by upregulating 14-3-3γ expression, inhibiting oxidative stress and inflammation, maintaining mitochondrial function, and protecting cardiomyocytes against LPS-induced injury.